KEMAMPUAN MENULIS TEKS EKSPLANASI PERISTIWA ALAM YANG BERSUMBER DARI MEDIA YOUTUBE OLEH SISWA SMA NEGERI 4 KOTA KUPANG TAHUN AJARAN 2025/2026 - Arliancy Baok; Labu Djuli; Samuel Nitbani (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2026)
This study aims to describe students’ ability to write explanatory texts on natural phenomena using YouTube as a learning medium. The research employed a descriptive qualitative method with class X-J students of SMA Negeri 4 Kupang as the subjects. Data were collected through writing tests, interviews, and documentation. Data analysis focused on text structure, content, and linguistic features of explanatory texts. The results indicate that students’ writing ability is categorized as good. A total of 29 students (85.29%) achieved mastery learning, while 5 students (14.71%) did not. Most students were able to write general statements, sequences of explanations, and apply appropriate linguistic features. Therefore, YouTube can be used as an effective learning resource to improve students’ explanatory writing skills.